Geological formations of the Mucuri river path in the State of Minas Gerais (International Journal of Geoscience, Engineering and Technology, 2020)
In this work, the geological formations along the Mucuri River in the State of Minas Gerais were identified in order to contribute to multidisciplinary engineering projects, mainly for the consolidation of urban, rural and environmental planning. The Mucuri River is formed by the junction of the Mucuri do Norte and Mucuri do Sul rivers. The first appears in the municipality of Malacacheta at 720m height and the second in the municipality of Ladainha at 750m of height. The processes of metamorphism and later weathering, associated to erosion, along the geological time, modelled the landscape of the region, transforming its territory with different heights. Many places in the region have quaternary alluvial soil suitable for growing grasses adapted to the flooding of the river. In the source of the South Mucuri River, in the municipality of Malacacheta, appear the Serra Negra Formation, belonging to the Guanhães Group, which consists of banded biotite-gneiss. The geological formations that follow the waterway of the Mucuri River have characteristics of Neoproterozoic rocks (late-tectonic granites of the Galiléia Intrusive Suite, of the Rio Doce Group), and of the Eocambrian (post-tectonic late granites of the Aimorés Intrusive Suite), aged 585 to 630 Ma. The eighteen formations found are respectively: Serra Negra Formation, Concórdia do Mucuri Formation, Leucogranite Caraí, Tumiritinga Formation (Marble), Tumiritinga Formation, Tonalite São Vitor, Topazio Granodiorite, Leucogranite Faísca, Wolff Granite, Caladão Granite, Charnockite Padre Paraíso, Kinzigitic gneiss, Leucogranite Carlos Chagas, Ataléia Granite, alluvial soil, Nanuque Granite, Underbite Mangalô and Granite Rio Mucuri.